Acoustic Study of the Nepali Nasal Consonants - Chalise, Krishna Prasad (Nepalese Linguistics, 2023)
The Nepali nasals have been characterized based on duration, formant structure, Cog, and SD. /n/ has the longest duration, followed by /m/ and /ŋ/. They are longer with homorganic vowels. The duration of each place of articulation remains constant across different vowel environments. N1 value increases from /m/ to /ŋ/ and N3 and N4 nearly follow the same pattern. BW1 is the largest for /ŋ/ followed by /m/ and /n/. Cog and SD do not correlate with place of articulation; rather, they correlate with the vowel environment. Similarly, amplitude does not distinguish a nasal from the adjacent vowel in all vowel environments.